Eye of the Red Tsar : a novel of suspense - Eastland, Sam (Eastland, Sam. Inspector Pekkala novel., 2010)
It is the time of the Great Terror. Inspector Pekkala - known as the Emerald Eye - was the most famous detective in all Russia. He was the favourite of the Tsar. Now he is the prisoner of the men he once hunted. Like millions of others, he has been sent to the gulags in Siberia and, as far as the rest of the world is concerned, he is as good as dead. But a reprieve comes when he is summoned by Stalin himself to investigate a crime. His mission - to uncover the men who really killed the Tsar and his family, and to locate the Tsar's treasure. The reward for success will be his freedom and the chance to re-unite with a woman he would have married if the Revolution had not torn them apart. The price of failure - death. Set against the backdrop of the paranoid and brutal country that Russia became under the rule of Stalin, "Eye of the Red Tsar" introduces a compelling new figure to readers of crime fiction.